The Latin Queen on the throne of 13th century Serbia. The Image of Helene d’Anjou in the writings of Archbishop Danilo II - Brzozowska, Zofia (Balcanica Posnaniensia. Acta et studia, 2012)
The main purpose of this article is to present one of the most interesting women in the history of medieval Serbia – Helene d’Anjou (Jelena Anžujska), the wife of the king Stefan Uroš I and the mother of Stefan Dragutin and Stefan Milutin. Queen Jelena’s origin has so far not been established with certainty. She is supposed to be the daughter of Raoul de Courtenay, the cousin of Louis IX of France, Charles d’Anjou, king of Naples and Baldwin, emperor of Constantinople after the Latin conquest. It is also important to confirm that she was a Catholic. The most reliable source of information about her life is the biography written by Danilo II, archbishop of the Serbian Orthodox Church. This is the only life of a woman that he wrote and is particularly valuable because Danilo knew Jelena personally and clearly liked and admired her.